KOMPOSISI JENIS POHON DI KAWASAN PELESTARIAN PLASMA NUTFAH (KPPN) ESTATE LANGGAM PT. RAPP - Sofan Sofiyanto; Defri Yoza; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Germ Plasm Preservation Area is a preservation area type in its original habitat in the production tree in order to preserve germ plasm both from plants and animals as well as microorganism. This research aims to know the tree variety composition and variety diversity index value in Germ Plasm Preservation Area of Langgam Estate. The data collection method used in this research is purposive sampling. Based on the obtained research result, variety composition in Germ Plasm Preservation Area is 37 varieties in 21 families in which Anacardiaceae family is the most abundant of 5 varieties. The index value of tree variety diversity obtained based on vegetation level is of 2.59 for seedling level, 2.89 for sapling level, 2.76 for staking level, and 2.86 for tree level. The tree variety diversity in Germ Plasm Preservation Area in every growth level is in medium category with 1 < H’ < 3. Keywords: Variety composition, Variety diversity, Preservation area